On the solar activity dependence of midnight equatorial plasma bubbles during June solstice periods. Issue 5 (22nd October 2021) - Ajith, K. K.; Ram, S. Tulasi; Li, GuoZhu; Yamamoto, M.; Hozumi, K.; Yatini, C. Y.; Supnithi, P.
Abstract: The occurrence of midnight Equatorial Plasma Bubbles (EPBs) during the June solstice period of the ascending phase of solar cycle 24, from 2010 to 2014, was studied using data from the 47 MHz Equatorial Atmosphere Radar (EAR) at Kototabang, Indonesia. The analysis shows that the occurrence of midnight hour EPBs was at its maximum during the low solar activity year 2010 and monotonically decreased thereafter with increasing solar activity. Details of the dependence of midnight hour EPB occurrence on solar activity were investigated using SAMI2 model simulation with a realistic input of E × B drift velocity data obtained from the CINDI‐IVM onboard the C/NOFS satellite. Results obtained from term‐by‐term analysis of the flux tube integrated linear growth rate of RT instability indicate that the formation of a high flux tube electron content height gradient (steep vertical gradient) region at higher altitudes, due to the elevated F layer, is the key factor enhancing the growth rate of RT instability during low solar activity June solstices. Other factors are discussed in light of the relatively weak westward zonal electric field in the presence of the equatorward neutral wind and north‐to‐south transequatorial wind around the midnight hours of low solar activity June solstices. Also discussed are the initial seeding of RT instability by MSTIDs and how the threshold height required for EPB development varies with solar activity. Key Points: The solar activity dependence on the occurrence of midnight EPBs were investigated during the ascending phase of solar cycle 24. The enhanced flux tube integrated growth rate of RT instability is observed during the low solar active June solstice. The elevated F layer and possible seeding by MSTIDs sets the conditions favorable during the low solar active summertime midnight hours.